Monodimensional and multidimensional character of frames in Anna Voitenko's photo cycle «Isa» as an element of author's communicative strategy - Antonova, Olha (My University, 2019)
The article is dedicated to the outline of the specifics of frame spatial organisation in documentary photo as an element of artist's communicative strategy and a mean of photo aesthetisation. Attention was paid to the study of current topical debate issue on the correlation of objective and subjective, artistic and documentary in photography, nature of reconsideration and means of reality modelling which are used by a photographer. The aim of the research was to explore the semantic potential of plan organisation of frame space in a documentary photo. The tasks of the article were to consider the palette of frame plan organisation in A. Voitenko's documentary cycle «Iza», to outline the significance acquired by frame spatial organisation as an expressive means in a documentary photo. The subject of the study includes the peculiarities of frame spatial organisation, and the object was the documentary series of photos «Iza» by Anna Voitenko. On the material of Anna Voitenko's documentary photo feature story «Iza» devoted to the depiction of life and mode of the inhabitants of a Transcarpathian village and their traditional handicraft, features of the application of monodimensional and multidimensional frame construction are considered. The article states the idea that a documentary photo is used to capture the reality reliably and accurately, but as any result of creativity, it carries the imprint of the author's worldview and evaluation of the depicted events, which can be expressed through particular compositional frame construction. The role and significance of monodimensional and multidimensional composition in Anna Voitenko's documentary frames as an element of artist's invention of the time and space continuum is analysed. It is emphasized that monodimensional, two-dimensional frame construction is most often used by A. Voitenko in case of depriving of depicted events of a clear binding to time, bringing them down to the level of a generalized symbol, attention concentration on key events and heroes of the documentary cycle. While multidimensional, three-dimensional compositional frame structure of documentary photos gives the opportunity to detail time and space of events, to saturate a frame with important details that serve to express the author's attitude to a depicted scene. The importance of the means used by the author to organize frame space, in particular, the point of shooting, the work with light and exposure solutions for silhouetting of images in monodimensional frames, the insertion of diagonals into a frame, and the visualization of a linear perspective for emphasis on multiplicity are considered, too. Other elements of compositional structure of documentary photos and their communicative and expressive potential requires further research. Keywords: documentary photo, frame space organisation, means of aesthetisation, monodimensional and multidimensional frame composition. Статтю присвячено окресленню специфіки просторової організації кадру в документальній фотографії як елементу комунікативної стратегії митця та засобу естетизації фото. Звернуто увагу на актуальні дискутивні питання про співвіднесення об'єктивного і суб'єктивного, художнього і документального у фотографії, про характер переосмислення та засоби моделювання дійсності фотографом. У статті обстоюється думка, що документальна фотографія покликана достовірно й точно зафіксувати дійсність, але, як будь-який результат творчості, несе відбиток авторського світобачення й оцінки зображуваних подій, виразником яких може виступати композиційна побудова кадру. Проаналізовано роль і значення однопланової та багатопланової композиції в документальних кадрах Анни Войтенко як елемента вибудування митцем часо-просторового континууму. Статья посвящена специфике пространственной организации кадра в документальной фотографии как элементу коммуникативной стратегии художника и средству эстетизации фото. Уделено внимание рассмотрению актуальных дискутивных вопросов о соотношении объективного и субъективного, художественного и документального в фотографии, о характере переосмысления и средствах моделирования действительности фотографом. В статье отстаивается мнение, что документальная фотография призвана достоверно и точно зафиксировать действительность, но, как любой результат творчества, несет отпечаток авторского мировоззрения и оценки изображаемых событий, выразителем которых может выступать композиционное построение кадра. Проанализированы роль и значение одноплановой и многоплановой композиции в документальных кадрах Анны Войтенко как элемента выстраивания художником время-пространственного континуума.
Keywords: документальна фотографія; documentary photography; засоби естетизації; means of aestheticization; просторова організація кадру; spatial organization of the frame; кафедра маркетингу